Teaching writing and discursive genres in the digital age: Results of a Writing Project - España Palop, Eduardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we present the results of a writing project based on Wikipedia article writing. This project was carried out with university students during the 21/22 academic year. The project consisted of the prototypical phases of this type of work: preparation for writing, writing and rewriting. During the project, an evaluation rubric was developed, which is the basis for the text analysis. This analysis has shown that students were able to acquire the necessary skills to achieve communicatively effective texts that meet the characteristics of the proposed genre.